2018
DOI: 10.1111/trf.14571
|View full text |Cite
|
Sign up to set email alerts
|

Blood product transfusion and wastage rates in obstetric hemorrhage

Abstract: Although the rates of receiving a transfusion of at least one blood product when one is ordered was high, many of the issued units were returned, especially for RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Cryoprecipitate is a nonpurified product; hence, in addition to fibrinogen it contains fibronectin and platelet microparticles, as well as coagulation factors VIII, XIII, and von Willebrand factor . Its fibrinogen content varies widely (from 3-30 g/L per unit); in most cases it must be maintained and shipped in a frozen state and then thawed and pooled (typically 5-10 unit pools) before administration; and it has a limited shelf life after thawing (<4-6 hours), increasing wastage . Fibrinogen concentrates are pathogen-reduced and purified; have standardized fibrinogen content (20 g/L); are lyophilized, allowing for easy storage, reconstitution, and administration; and have longer shelf life after reconstitution (up to 24 hours), which reduces wastage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryoprecipitate is a nonpurified product; hence, in addition to fibrinogen it contains fibronectin and platelet microparticles, as well as coagulation factors VIII, XIII, and von Willebrand factor . Its fibrinogen content varies widely (from 3-30 g/L per unit); in most cases it must be maintained and shipped in a frozen state and then thawed and pooled (typically 5-10 unit pools) before administration; and it has a limited shelf life after thawing (<4-6 hours), increasing wastage . Fibrinogen concentrates are pathogen-reduced and purified; have standardized fibrinogen content (20 g/L); are lyophilized, allowing for easy storage, reconstitution, and administration; and have longer shelf life after reconstitution (up to 24 hours), which reduces wastage.…”
Section: Introductionmentioning
confidence: 99%
“…6 Its fibrinogen content varies widely (from 3-30 g/L per unit); in most cases it must be maintained and shipped in a frozen state and then thawed and pooled (typically 5-10 unit pools) before administration; and it has a limited shelf life after thawing (<4-6 hours), increasing wastage. 7,8 Fibrinogen concentrates are pathogen-reduced and purified; have standardized fibrinogen content (20 g/L); are lyophilized, allowing for easy storage, reconstitution, and administration; and have longer shelf life after reconstitution (up to 24 hours), which reduces wastage. There is divergent practice regarding the preferred product for fibrinogen replacement.…”
mentioning
confidence: 99%
“…For the above reasons, we still see a role for an MTP in any paediatric institution, despite the limited evidence. However, wastage may potentially follow the implementation of an MTP, and many centres have reported an increase in blood wastage rates following its implementation [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upon returning the product to the blood bank, the products are often outside of acceptable temperature ranges, making it unsafe for it to be diverted to other patients [ 6 ]. Wastage rates in adult studies are reported to range from 2–7% [ 11 , 13 ]. Our institution’s wastage rate is at 1.5%, which is a comparatively low figure.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of cryoprecipitate into MTPs has led not only to increased demand for product but also to a disproportionate increase in wastage. This is because, unlike thawed plasma, cryoprecipitate has a shelf life of only 4 or 6 hours after thawing, which precludes its reuse if returned to the blood bank after being issued as part of an MTP 22,23 . Even with the increase in wastage, management of cryoprecipitate inventory to allow for strict adherence to ABO compatibility has not often presented the same challenges as that of platelets and AB plasma, until now.…”
mentioning
confidence: 99%